Bone Marrow Involvement in Patients With Nodular Lymphocyte Predominant Hodgkin Lymphoma. (April 2018) - Agbay, Rose Lou Marie C.; Loghavi, Sanam; Zuo, Zhuang; Fayad, Luis; Dabaja, Bouthaina; Medeiros, L. Jeffrey; Khoury, Joseph D.
Abstract : The spectrum of bone marrow lesions in patients with nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) has not been evaluated systematically. In this study, we analyzed a cohort of 262 NLPHL patients who underwent staging bone marrow evaluation or targeted bone biopsy as a part of their initial diagnostic workup, among which lymphoma was detected in 24 (9.2%) patients. Eleven patients had bone marrow findings of NLPHL (few large B cells in a background of small B cell and T cell), and 13 patients had either T-cell/histiocyte-rich large B-cell lymphoma (large B cells in a background of T cells and histiocytes) or typical diffuse large B-cell lymphoma (sheets of large B cells). Bone marrow involvement was more common in patients with variant NLPHL histologic patterns in the lymph node as compared with those who had classic patterns (12/18 vs. 4/16; P= 0.02). An additional 27 NLPHL patients had bone marrow specimens involved by lymphoid aggregates composed of small T cells and B cells without large B cells; this subgroup had a longer event-free survival than patients with lymphoma in the bone marrow (145 vs. 35 mo). Disease recurrence or progression was more frequent in patients with bone marrow involvement by either NLPHL or LBCL, compared with patients who had lymphoid aggregates (13/21 vs. 8/26; P= 0.04). In conclusion, staging bone marrow sampling detects lymphoma in a sizeable subset of NLPHL patients, particularly those with variant histologic patterns. Lymphoid aggregates lacking large B cells in staging bone marrow specimens from NLPHL patients can be regarded as clinically benign without impact on stage, outcome, or risk stratification. Abstract : Supplemental Digital Content is available in the text.